Mind Mapping Sebagai Metode Alternatif Pembelajaran Akidah Akhlak - Nabila; Ida Faridatul Hasanah (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2022)
The teaching and learning process is the core of educational activities in schools. The teacher has a role as an educator, besides being a facilitator in teacher learning as well as a guide. In the teaching and learning process, one of the factors that strongly supports the success of teachers in carrying out learning is the teacher's ability to master and apply learning methods that can improve student learning outcomes. This study aims to determine the application of the mind mapping to learning aqidah morals. This study uses qualitative research with the type of classroom action research (PTK). The population is a population of 667 students and a sample of 29 students. The results of this research are that the Mind Mapping can improve student learning outcomes in the learning process of aqidah morals. In the first cycle the average score of student learning outcomes was 77.24 and 62.07% completeness, and in the second cycle the average score of student learning outcomes was 80.68 with a completeness percentage of 82.76%, so that the mind mapping can be used as an alternative in the learning process moral theology.